Computational simulation of petrol behavior (SWIRL) inside combustion chamber during the intake-stroke using fluent / Shafie Omar - Omar, Shafie (2005)
This thesis is presenting the development of computational simulation of petrol behavior inside combustion chamber during the intake-stroke by using fluent. The validation has been conducted using experimental analysis. The data that had been simulated are collected from the experiment done in laboratory. The validation of the result from simulation had been done by comparing with theoretical that stated in the book. The results analyses are base on the difference speed of engine. The swirl phenomenon is proportional to the velocity of fuel that applies to the intake manifold. The higher the velocity of fuel flow into the combustion chamber the more swirl phenomena occur inside combustion chamber.